2019
DOI: 10.3390/su11102774
|View full text |Cite
|
Sign up to set email alerts
|

A Study of the Pedestrianized Zone for Tourists: Urban Design Effects on Humans’ Thermal Comfort in Fo Shan City, Southern China

Abstract: Ling Nan Tian Di block is in Fo Shan city, which is in the hot-summer and warm-winter climate area of China and is a very important scenic spot. A pedestrianized zone aims to provide a commercial and recreational center for tourists. The utilization of it is determined by the outdoor microclimate, which affects not only humans’ thermal sensation but also the commercial value; thus, putting forward the best time of day to visit this region in extreme summer is very necessary. Using the result of this work, tour… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 13 publications
(11 citation statements)
references
References 55 publications
0
11
0
Order By: Relevance
“…After that, we put forward some scientific hypotheses to understand the effect of different mentioned urban design parameters in cooling the thermal environment, this helps to the select the nest strategy to improve people's thermal comfort and health. that a lower SVF brings lower daytime temperatures in canyon space [9]. In addition, SVF also affects the level of the wind speed, and a study found that a 10% increase in SVF will lead to an 8% increase in wind speed [10].…”
Section: The Methodological Frameworkmentioning
confidence: 99%
See 1 more Smart Citation
“…After that, we put forward some scientific hypotheses to understand the effect of different mentioned urban design parameters in cooling the thermal environment, this helps to the select the nest strategy to improve people's thermal comfort and health. that a lower SVF brings lower daytime temperatures in canyon space [9]. In addition, SVF also affects the level of the wind speed, and a study found that a 10% increase in SVF will lead to an 8% increase in wind speed [10].…”
Section: The Methodological Frameworkmentioning
confidence: 99%
“…The second factor is the sky view factor (SVF), which is expressed as "the ratio of the sky which can be seen from a stable position on a surface to that potentially available" [8], this index is a number ranging from 0 to 1. A previous study has shown that a lower SVF brings lower daytime 2 of 19 temperatures in canyon space [9]. In addition, SVF also affects the level of the wind speed, and a study found that a 10% increase in SVF will lead to an 8% increase in wind speed [10].…”
Section: Introductionmentioning
confidence: 98%
“…The simulated model of the selected site is shown in Figure 6. The classification of thermal perception and PET values of the hot summer and warm winter climate zone is shown in Table 4 [45,46]. The simulated model of the selected site is shown in Figure 6.…”
Section: Numerical Simulationmentioning
confidence: 99%
“…Table 4. The physiological equivalent temperature (PET) values and humans' thermal perceptions [45,46].…”
Section: Numerical Simulationmentioning
confidence: 99%
See 1 more Smart Citation